2005
DOI: 10.1111/j.1365-2621.2005.tb09038.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Saturated Acyl L-Ascorbates in Aqueous Solution

Abstract: acid, which was formed through the hydrolysis of the ester bond in the ascorbate, was measured at pH decanoic acid, which was formed through the hydrolysis of the ester bond in the ascorbate, was measured at pH decanoic acid, which was formed through the hydrolysis of the ester bond in the ascorbate, was measured at pH decanoic acid, which was formed through the hydrolysis of the ester bond in the ascorbate, was measured at pH decanoic acid, which was formed through the hydrolysis of the ester bond in the asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Saturated derivative esters were more stable than the unsaturated ones both in acidic and neutral conditions. In acidic condition, L‐AD and L‐AP showed better stability than L‐AA, this result was in agreement with a previous study that L‐AD was more stable than L‐AL and L‐AN at pH 3 (Kuwabara and others ). In neutral condition, L‐AP showed the best stability among the saturated derivative esters and showed a similar stability as L‐AA.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Saturated derivative esters were more stable than the unsaturated ones both in acidic and neutral conditions. In acidic condition, L‐AD and L‐AP showed better stability than L‐AA, this result was in agreement with a previous study that L‐AD was more stable than L‐AL and L‐AN at pH 3 (Kuwabara and others ). In neutral condition, L‐AP showed the best stability among the saturated derivative esters and showed a similar stability as L‐AA.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies reported that derivatives of L‐AA such as l ‐ascorbyl benzoate and l ‐ascorbyl palmitate (L‐AP), with good solubility in hydrophobic medium, showed similar or even better antioxidant effects than L‐AA (Burham and others ). Some researchers reported that l ‐ascorbyl fatty acid esters like L‐AP and l ‐ascorbyl stearate (L‐AS) could be used to replace the traditional antioxidants in food and cosmetic industry (Humeau and others ; Kuwabara and others ). l ‐Ascorbyl fatty acid esters were normally synthesized by chemical method in corrosive solvent containing sulfuric acid or hydrofluoric acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two possible explanations exist for this observation. One is degradation of the erythorbyl moiety of the erythorbyl laurate, and the other possibility is hydrolysis of the ester bond in the erythorbyl laurate . Therefore, to investigate the instability of erythorbyl laurate at a high temperature, the degradation of the compound was monitored during storage at 70°C and 90°C using HPLC.…”
Section: Resultsmentioning
confidence: 99%
“…One is degradation of the erythorbyl moiety of the erythorbyl laurate, and the other possibility is hydrolysis of the ester bond in the erythorbyl laurate. 35 Therefore, to investigate the instability of erythorbyl laurate at a high temperature, the degradation of the compound was monitored during storage at 70 C and 90 C using HPLC. A peak of released erythorbic acid or lauric acid from erythorbyl laurate was rarely detected during the storage (data not shown), indicating the low storage stability of erythorbyl laurate at such high temperatures, which was likely due to thermal degradation, rather than hydrolysis of the ester bond.…”
Section: Storage Stability Of Erythorbyl Lauratementioning
confidence: 99%